Two-and tridimensional analysis of periapical repair after endodontic surgery - Tanomaru-filho, Mário [UNESP]; Jorge, Érica G. [UNESP]; Guerreiro-Tanomaru, Juliane M. [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP]; Spin-Neto, Rubens; Gonçalves, Marcelo [UNESP] (Springer Nature, 2015)
Objective The aim of this study was to evaluate repair after endodontic surgery using two- and tridimensional imaging methods. Materials and methods Periapical radiographs and cone beam computed tomography (CBCT) were performed before the surgeries and after 48 h (baseline), 4 months, and 8 months. The area (square millimeters) of periapical lesions in CBCT and in radiographs was compared regarding the percentage of repair. In the CBCT, multiple areas were converted to volume. Repeated-measures analyses and paired t tests (α=0.05) were used to compare the methods. Correlation coefficients were calculated between the periods of evaluation within the CBCT volumetric analysis. Bland-Altman plots were used to compare the methods, based on the 95 % limits of agreement for the difference of the means. Results Baseline showed a larger lesion volume (192.54 mm3 ) than 4-month (79.79 mm3 ) and 8-month (47.51 mm3 ) periods. No differences were found in the percentage of repair in the first 4 months and after 8 months. The volumetric analysis showed a higher percentage of repair when the first and last 4 months were compared. No differences were found in the percentage of repair by area in the CBCTs. Repair of 73 % was obtained after 8 months. Similar results were observed by the Bland-Altman agreement analyses. Conclusions The percentage of repair varied after 8 months, when lower values were obtained by volumetric evaluation. Clinical relevance Considering the outcome at follow-up periods over 4 months, tridimensional evaluation by CBCT is more capable of determining the absence of periapical bone repair than conventional two-dimensional radiographs. Therefore, the use of CBCT would be suggested only for more complex cases with slower evolution of repair or for the association of factors that make prognosis difficult after surgery.
Keywords: Periapical repair; Tridimensional analysis; CBCT; Endodontic surgery